2015
DOI: 10.21890/ijres.71245
|View full text |Cite
|
Sign up to set email alerts
|

Seventh Grade Students’ Problem Solving Success Rates on Proportional Reasoning Problems

Abstract: This research was conducted to investigate 7th grade students' problem solving success rates on proportional reasoning problems and whether these success rates change with different problem types. 331 randomly selected students of grade seven participated in this study. A problem test which contains three different types of missing value (direct proportional, inverse proportional and additive/non-proportional) word problems was designed as a data collecting tool for the research. Descriptive data analysis meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
1
2
0
1
Order By: Relevance
“…Additionally, it was concluded that problem types affected students' solution strategies. Similar results were reported by Pelen and Artut (2016) who investigated seventh grade students' problem-solving performances on some proportional and non-proportional problems. They found that problem types affected students' problem-solving performances.…”
Section: Literature Reviewsupporting
confidence: 86%
See 1 more Smart Citation
“…Additionally, it was concluded that problem types affected students' solution strategies. Similar results were reported by Pelen and Artut (2016) who investigated seventh grade students' problem-solving performances on some proportional and non-proportional problems. They found that problem types affected students' problem-solving performances.…”
Section: Literature Reviewsupporting
confidence: 86%
“…Furthermore, students were more successful in solving missing value problems than the other types of problems. Similarly, research studies reported that problem types affected students' solution strategies and problem-solving performances (Duatepe et al, 2005;Kayhan, 2005;Özgün-Koca & Kayhan-Altay, 2009;Pelen & Artut, 2016). Furthermore, the findings of the study revealed that students' success rates were changed according to the context of the problems.…”
Section: Conclusion and Discussionmentioning
confidence: 55%
“…Students who do not understand the use of ratios and proportions cannot work on missing value problems. Students have difficulty solving one type of proportion problems, that is missing value problems (Pelen & Artut, 2016). Students with a low level of mathematical ability cannot reason according to the context of the problem given.…”
Section: Discussionmentioning
confidence: 99%
“…Proporsi diartikan sebagai kesamaan dua rasio dalam bentuk 𝑎 𝑏 = 𝑐 𝑑 [2]. Pada bentuk proporsi tersebut, apabila terdapat salah satu nilai yang hilang, maka disebut dengan masalah missing value (nilai yang hilang) [3]. Misal ketika diketahui tiga nilai 𝑎, 𝑏, dan 𝑐 dari proporsi 𝑎: 𝑏 = 𝑐: 𝑑, maka siswa diminta untuk mencari nilai 𝑑 [4].…”
Section: Pendahuluanunclassified